2022
DOI: 10.1177/05390184231158210
|View full text |Cite
|
Sign up to set email alerts
|

All power to the reviewers: British sociology under two-level supervision of the Research Excellence Framework

Abstract: Our study investigates the impact of the British Research Assessment Exercise in 2008 and Research Excellence Framework in 2014 on the diversity and topic structure of UK sociology departments from the perspective of habitus-field theory. Empirically, we train a Latent Dirichlet allocation on 819,673 abstracts stemming from the journals in which British sociologists submitted at least one paper in the Research Assessment Exercise 2008 or Research Excellence Framework 2014. We then employ the trained model on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Overall, it is a highly visible and influential system, which has been debated and studied intensively. For example, recent studies have argued that the REF has led to a homogenization of research in several fields (Pardo-Guerra, 2022), yet as shown by Wieczorek et al. (this volume), the concrete epistemological effects of the system are difficult to determine.…”
Section: Four Distinct Shapes Of National Research Performance Measur...mentioning
confidence: 99%
“…Overall, it is a highly visible and influential system, which has been debated and studied intensively. For example, recent studies have argued that the REF has led to a homogenization of research in several fields (Pardo-Guerra, 2022), yet as shown by Wieczorek et al. (this volume), the concrete epistemological effects of the system are difficult to determine.…”
Section: Four Distinct Shapes Of National Research Performance Measur...mentioning
confidence: 99%